Digitalization and change in the global division of labor: Industrial work in transition - Martin Krzywdzinski (RBEST: Revista Brasileira de Economia Social e do Trabalho, 2021)
The contribution discusses the impact of digitalization approaches in industrial companies and their implications for the global division of labour and work. It proceeds by investigating the scope and character of automation and its impact on the relationship between production locations in high and low wage countries. Contrary to expectations frequently voiced in public discourse the author does not identify a major push in automation in manufacturing industries (that would make a reshoring of production viable), because digitalization strategies rather concern new paths of flexibilization than automation. The effects on the geographies of production of technological change, however, result in new strategies of specialization and modifications of industrial governance, namely a refined division of labour between innovation-intensive production sites and their counterparts in the periphery. – – El artículo examina hasta qué punto el mercado de trabajo se está viendo afectado por los procesos de digitalización y automatización, tomando como base material empírico sobre la industria automovilística alemana. El objetivo es debatir tres cuestiones: (1) Qué dinámica de cambio en los conceptos de automatización puede observarse y qué efectos en el cambio de la división del trabajo entre lugares con salarios altos y bajos cabe esperar? (2) Cómo están cambiando las estrategias de localización de las empresas, las estructuras de empleo y las necesidades de cualificación y hasta qué punto existen peligros de externalización de la producción? (3) En qué medida están cambiando la gobernanza industrial y las cadenas de valor internacionales como resultado de la evolución hacia modelos empresariales basados en datos? El argumento se centra en la transición que se ha producido en el sector automovilístico. Además de las fuentes estadísticas generales, se utiliza en particular
Keywords: D20; J21; J31; L23; L62; O33; 330; automation; automotive industry; global value chains; Germany; automatización; industria del automóvil; cadenas de valor mundiales; Alemania